MUSLIM NEGARAWAN: TELAAH ATAS PEMIKIRAN DAN KETELADANAN BUYA HAMKA - Andi Saputra (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2019)
One of the primary values inherent in the personality of the nation (founding father) in addition to the breadth of insight is the strong pas- sion and love for the homeland nationality. Philosophy of life that stands on the foundation of nationalism and patriotism that is then color every movement, behavior as well as the epic struggle deeds they do, for the grounding the ideals of independence. Along with that, especially in the context of the independence of the nation, teaching in the form of ideas and ideals that appear to be important life values for the next generation. Besides an attempt to take the essence of the teaching given, also related to the effort to continue to foster national values and love of the homeland as the ethical foundation in terms of bringing the nation to the gates of progress. One in a series of well-known national leader is Haji Abdul Malik Karim Amrullah (Hamka); a statesman who thinks that nation- alism and patriotism as part of the faith (religion). Through a sociolog- ical theory of knowledge Mannheim has found that important teaching presented Hamka in relation to the life of the nation that is their re- sponsibility that must be realized that every citizen. Responsibilities shall include nationality, homeland, all of which according to Hamka in line with the main principles of Islam, namely amar ma’ruf nahi munkar. Such a principle is not limited to maintaining dignity according to the nation. Furthermore, a sense of nationalism and love for the homeland is the main asset that can make a race higher than other nations.